Clinical and Biochemical Evaluation of the Use of Alb-PRF versus L-PRF in Mandibular Third Molar Extractions: A Split-Mouth Randomized Clinical Trial - Kayvon Javid; Carlos Fernando Mourão; Rafael Coutinho Mello-Machado; Suelen Cristina Sartoretto; Madelaine Torres; Emanuelle Stellet Lourenço; Paulo Emilio Correa Leite; José Mauro Granjeiro; Gutemberg Gomes Alves; Monica Diuana Calasans-Maia (Journal of Functional Biomaterials, 2023)
Bone tissue engineering seeks biomaterials that enable cell migration, angiogenesis, matrix deposition, and tissue regeneration. Blood concentrates like platelet-rich fibrin (L-PRF) offer a cost-effective source of cells and growth factors to enhance healing. The present study aimed to evaluate heated serum albumin with liquid PRF (Alb-PRF) and L-PRF clinically and biochemically after placement in dental sockets following mandibular third molar extraction. In a controlled, split-mouth study involving 10 volunteers, 20 extracted molars were treated with either Alb-PRF or L-PRF. Post-extraction, pain, trismus, infection presence, and swelling were measured. The concentrations of different analytes in the surgical sites were also examined. The data were statistically analyzed, with significance defined at p < 0.05 (t-test). No significant difference was noted between the groups for pain and trismus, but Alb-PRF showed a significant reduction in swelling on day seven. The Alb-PRF group showed lower levels of pro-inflammatory cytokines (GM-CSF, IL-1b, IL-6, IFNy, IL-8, IL-15, RANTES, and MIP-1a) after seven days, with only higher expressions of MIP-1b, IL-1b, and MCP-1 found in the L-PRF group. Differences were observed in the release of analytes between L-PRF and Alb-PRF, with Alb-PRF significantly reducing edema after seven days. Alb-PRF reduced edema, while L-PRF increased inflammatory cytokines. When compared to L-PRF, Alb-PRF reduced edema and the release of inflammatory cytokines, suggesting promising effects in socket healing while underscoring the role of growth factors and cytokines in potential applications of blood concentrates.